Proteomic expression profile of injured rat peripheral nerves revealed biological networks and processes associated with nerve regeneration. Issue 8 (9th March 2018) - Vergara, Daniele; Romano, Alessandro; Stanca, Eleonora; La Pesa, Velia; Aloisi, Laura; De Domenico, Stefania; Franck, Julien; Cicalini, Ilaria; Giudetti, Anna; Storelli, Elisa; Pieragostino, Damiana; Fournier, Isabelle; et al.
Abstract : Peripheral nerve regeneration is regulated through the coordinated spatio‐temporal activation of multiple cellular pathways. In this work, an integrated proteomics and bioinformatics approach was employed to identify differentially expressed proteins at the injury‐site of rat sciatic nerve at 20 days after damage. By a label‐free liquid chromatography mass‐spectrometry (LC‐MS/MS) approach, we identified 201 differentially proteins that were assigned to specific canonical and disease and function pathways. These include proteins involved in cytoskeleton signaling and remodeling, acute phase response, and cellular metabolism. Metabolic proteins were significantly modulated after nerve injury to support a specific metabolic demand. In particular, we identified a group of proteins involved in lipid uptake and lipid storage metabolism. Immunofluorescent staining for acyl‐CoA diacylglycerol acyltransferase 1 (DGAT1) and DAGT2 expression provided evidence for the expression and localization of these two isoforms in Schwann cells at the injury site in the sciatic nerve. This further supports a specific local regulation of lipid metabolism in peripheral nerve after damage. Abstract : In this work, an integrated proteomics and bioinformatics approach was employed to identify differentially expressed proteins at the injury‐site of rat sciatic nerve at 20 days after damage. By a label‐free liquid chromatography‐mass spectrometry (LC‐MS/MS) approach, we identified 201 differentially proteins that were assigned to specific canonical and disease and function pathways. Metabolic proteins were significantly modulated after nerve injury to support a specific metabolic demand.